Análisis de la incidencia de la Certificación Comercio Justo en las Exportaciones de Banano Ecuatoriano. Periodo 2012-2022 - Sojos Peralta Sheyla Aeleen (2023)
This research delves into the connection between Fair Trade certification and the burgeoning banana industry in Ecuador. In pursuit of a more equitable and just trading scenario, the actual impact of such certification over the last decade in Ecuador is scrutinized. Despite a marked increase in interest towards Fair Trade, its impact, so far, has been relatively modest and limited in the sector. The study adopts a primarily quantitative approach, using a non-experimental and longitudinal analysis of a descriptive nature. Among the main obstacles identified are the high certification costs, a tangible lack of information on the subject, and a perception that the derived benefits are marginal. Through a meticulous literature review, combined with the analysis of already certified farms and the evaluation of fluctuations in export prices and volumes, the study concludes that only a minority fraction of exports truly adopts the guidelines of Fair Trade. These findings underscore the urgency to thoroughly investigate existing barriers and to devise effective strategies to encourage a broader adoption of this certification